The Impact of Nature Relatedness on Environmental Attitudes Weakens among Materialistic Individuals: Evidence from the Philippines - Aruta, John Jamir Benzon R. (Animo Repository, 2022)
Although there exist separate lines of research showing that nature relatedness and materialism independently promote and/or hinder environmentalism, little research has looked at the influence of these two psychological factors on people’s environmental attitudes when examined in concert with each other. This is important because in reality, psychological constructs operate simultaneously and often interactively within a person. The current research investigated the moderating role of materialism on the positive impact of nature relatedness on environmental attitudes in Filipino adults within the context of massive environmental degradation and modernization in the Philippines. Using a cross-sectional online survey, data were collected from 373 females and 216 males (mean age = 30.06, SD age = 13.31) in urban areas in Metro Manila, Philippines. Findings revealed that materialism moderated the positive impact of nature relatedness on environmental attitudes. Specifically, the positive impact of nature relatedness on environmental attitudes was strong among people with lower levels of materialism and weak among those with moderate levels and diminishes among people with high levels of materialistic values. The present findings offer novel insights on how materialistic values could suppress the influence of nature relatedness as a promoting factor in encouraging environmental attitudes. Limitations, future directions, and implications are discussed.